Location and volume of MRI artifacts in patients with implanted sphenopalatine ganglion neurostimulators for treatment of chonic cluster headache - Jakobs, Martin; Jesser, Jessica; Albrecht, Tobias; Wick, Antje; Unterberg, Andreas; Ahmadi, Rezvan (Neuromodulation, 2019)
Introduction Sphenopalatine ganglion stimulation (SPG-S) is an invasive form of neuromodulation by which a neurostimulator is implanted into the pterygopalatine fossa to treat refractory chronic cluster headache. The implant is MRI conditional, up to 3 T, however there is no clinical data on the shape, size, and location of the artifact produced by the implant. Materials and Methods Records of patients with SPG-S were analyzed for postoperative cranial MRI scans. MRI and intraoperative CT scans for visualization of the implant were fused and volumetry was performed for both the implant and the MRI artifact in different MRI sequences. Results In total, n = 3 patients with postoperative MRI scans were identified. The mean CT artifact volume was 0.73 cm3 (±0.15 cm3). MRI artifact volume differed between sequences (range: 25.2-220.7 cm3). The intracranial space was largely unaffected besides the pole of the ipsilateral temporal lobe and the basal frontal gyrus. MRI artifacts affected the extracranial space (orbit, maxillary and ethmoid sinuses, and parts of the parotid gland). No adverse events occurred during or after MRI scans. Conclusions Cranial MRI scans with SPG-S implants were safely performed in three patients following the manufacturer's MRI conditions. MRI artifacts were mostly located in the extracranial space. Brain MRI imaging is largely unaffected. Conflict of Interest The authors declare no potential conflicts of interest with respect to research, authorship, and/or publication of this article.
Version of record online: 30 September 2018
Gesehen am 26.02.2020